W kręgu historiografii czasów saskich - Prabucki Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The review describes Piotr Sebastian Ślusarczyk’s book entitled “Horizons of erudition. A study on Szymon Majchrowicz’s Triazoic szczęśliwa królestw”. The cognitive value of this publication is manifested in its extraordinary approach to historiographic matter which is extremely often marginalized by researchers studying the late Baroque literary heritage. The review focuses on showing the erudite nature of Ślusarczyk’s monograph first of all and also examining the antecedents of the ideas explicated in the Jesuit’s work and also polemics with the author about the „Sarmatian nature” of Szymon Majchrowicz’s treatise.
In the Circle of Historiography at the Saxon Times
Recenzja monografii: Piotra Sebastiana Ślusarczyka „Horyzonty erudycji. Studium o „Trwałości szczęśliwej królestw Szymona Majchrowicza”, Dom Wydawniczy Elipsa, Warszawa 2021, 234 ss.
Keywords: Sarmatism; Szymon Majchrowicz; Jesuits; historiosophy; sarmatyzm; jezuici; historiozofia